Future tense—Reorienting higher education toward an unknown future - Cruz, Laura; Morkel, Jolanda; Gachago, Daniela (Frontiers in Communication, 2022)
In view of the recent pandemic and growing wicked problems associated with an uncertain, complex and unknown future, this paper explores academics’ conceptualizations of the future. Inspired by Kuhn, we chose the academic conference as a public sphere where members of small networks of trusted peers and other such micro-communities gather, creating and recreating the past, present, and future through conversation and collaboration as the site of this paper. We thematically analyzed 83 calls from 39 conferences covering four English-speaking regions: North America, Europe, Africa and Australia/International and five different conference foci, including Teaching and Learning, SOTL, academic staff/faculty development, educational technology and Future Conferences, from 2019 to 2022. Applying thematic analysis, two main themes emerged in relation to the future: Responsiveness and Temporality. Responsiveness is reflective of the currently dominant neo-liberal paradigm, which seeks to foster incremental adaptations to changing conditions whereas Temporality is indicative of more fundamental shifts in thinking, not just considering what the future may hold, but deeper changes in the relationship between universities and their past, present, and future.